2006
DOI: 10.1007/s00208-006-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

On a problem of Bremermann concerning Runge domains

Abstract: In this paper we give an example of a bounded Stein domain in C n , with smooth boundary, which is not Runge and whose intersection with every complex line is simply connected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is proved in [9] (in [20] for linear case) that any spirallike domain with respect to an asymptotically stable vector field is Runge. But, in view of Joit ¸a [27], this does not imply the closure of the domain, in case the domain is bounded, is polynomially convex. Hamada also provided an example in [21] showing that strictly spirallike is crucial, even in case the vector field is linear.…”
Section: Introduction and Statements Of The Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is proved in [9] (in [20] for linear case) that any spirallike domain with respect to an asymptotically stable vector field is Runge. But, in view of Joit ¸a [27], this does not imply the closure of the domain, in case the domain is bounded, is polynomially convex. Hamada also provided an example in [21] showing that strictly spirallike is crucial, even in case the vector field is linear.…”
Section: Introduction and Statements Of The Resultsmentioning
confidence: 98%
“…However, in [26,Example 2.7], it was shown that the closure of a bounded strongly pseudoconvex domain with a smooth boundary may not be polynomially convex. In [27], Joit ¸a gave an example of a strongly pseudoconvex domain in C n with real analytic boundary whose closure is not polynomially convex. The doamin in the example of Joit ¸a [27] is a is also a Runge domain.…”
Section: Introduction and Statements Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Is it true that D is Runge in C n ?". Negative answers to this problem have also recently been given in [1] and [5]. On can infact show, using an argument as above together with the argument principle, that if R is a smoothly bounded planar domain and if ϕ(R) is a holomorphic embedding of R into C 2 with ϕ(∂R) ⊂ , then ϕ(R) ⊂ .…”
Section: Introductionmentioning
confidence: 99%